Implants for surgery - wear of total knee-joint prostheses - part 3: loading and displacement parameters for wear-testing machines with displacement control and corresponding environmental conditions for test (ISO 14243-2:2004, COR. 1:2006, IDT) - Abdul Razak, Noor Hayati; Yaakop, Salbiah; Choon, David; Goonting, Tracy E.; T, Mahadevan; Law, Ching Yee; How, Kim Chuan; Singh, Harwant; Ismail, Zulkharnain; Manickam, Thirumal; Yaakob, Mohd Amin; Mohd Yusof, Hyzan; et al. (SIRIM, 2011)
This Malaysian Standard specifies relative movement between articulating components, the pattern of the applied force, speed and duration of testing, sample configuration and test environment to be used for the wear testing of total knee-joint prostheses in wear-testing machines having axial load control, flexion/extension angular motion control, AP displacement control and tibial rotation control.